Severe Human Granulocytic Anaplasmosis With Significantly Elevated Ferritin Levels in an Immunocompetent Host in Pennsylvania: A Case Report - Mona L. Camacci MD, MSc; Ronaldo Paolo Panganiban BA; Zachary Pattison DO, MPH; Kamyar Haghayeghi DO; Alexander Daly MD; Cindy Ojevwe MD; Ryan J. Munyon MD (SAGE Publishing, 2018)
Human granulocytic anaplasmosis (HGA) is a tick-borne, infectious disease caused by Anaplasma phagocytophilum that generally presents with nonspecific symptoms such as fever, chills, headache, malaise, and myalgia. If not treated immediately, HGA can cause hemophagocytic lymphohistiocytosis (HLH), a well-documented but underrecognized sequela of severe HGA. In this article, we report a case of severe HGA with hyperferritinemia in a 74-year-old male from Central Pennsylvania who initially presented with recurrent fevers, nausea, and malaise to our emergency department and was subsequently discharged home that same day. Ten days later, the patient returned with acute kidney injury, elevated liver transaminases, and profound hyperferritinemia to 5130 ng/mL. Empiric doxycycline was administered for suspected tick-borne disease and serologies eventually came back positive for anti- Anaplasma phagocytophilum antibodies. The patient returned to baseline status 15 days after discharge. Our case shows the challenges in the timely diagnosis of HGA and highlights the role of serum ferritin in aiding this diagnosis. Although our patient did not fulfill the HLH diagnostic criteria, our report demonstrates the importance of recognizing HGA as a reversible cause of HLH.